Polyomavirus origin for DNA replication comprises multiple genetic elements. - Muller, W J (1983)
To define the minimal cis-acting sequences required for polyomavirus DNA replication (ori), we constructed a number of polyomavirus-plasmid recombinants and measured their replicative capacity after transfection of a permissive mouse cell line capable of providing polyomavirus large T antigen in trans (MOP cells). Recombinant plasmids containing a 251-base-pair fragment of noncoding viral DNA replicate efficiently in MOP cells. Mutational analyses of these viral sequences revealed that they can be physically separated into two genetic elements. One of these elements, termed the core, contains an adenine-thymine-rich area, a 32-base-pair guanine-cytosine-rich palindrome, and a large T antigen binding site, and likely includes the site from which bidirectional DNA replication initiates. The other, termed beta, is located adjacent to the core near the late region and is devoid of outstanding sequence features. Surprisingly, another sequence element named alpha, located adjacent to beta but outside the borders of the 251-base-pair fragment, can functionally substitute for beta. This sequence too contains no readily recognized sequence features and possesses no obvious homology to the beta element. The three elements together occupy a contiguous noncoding stretch of DNA no more than 345 base pairs in length in the order alpha, beta, and core. These results indicate that the polyomavirus origin for DNA replication comprises multiple genetic elements.